Penanaman Karakter Bersahabat melalui Cerita Anak Menggunakan Audio Book Difalitera pada Anak Usia 4-6 Tahun - Mubayyamah; A. Shafir Ubaidillah; Moh. Badrih; Ari Ambarwati (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
in early childhood through stories using difalitera voice literature in children aged 4-6 years at the Griya Belajar Malang Tutoring. The design in this research uses qualitative field methods with data collection techniques using observation, documentation and interviews. The data obtained were the results of interviews with tutors and student guardians as well as the results of direct observations, and documentation in daily report books of children's activities at school. The objects in this research are children aged 4-6 years who receive Calistung tutoring at the Griya Belajar Malang tutoring. Data analysis techniques are carried out by means of data reduction, data display and drawing conclusions. The results of this research are a description of the process of implementing friendly character development in early childhood, namely a description of the implementation of learning for 90 minutes which is divided into several materials, namely reading, writing, arithmetic and listening to stories using difalitera sound literature. Then there are factors that become obstacles and supporters in this implementation, namely parental support, the attractiveness of the story, the conduciveness of the learning environment, and physical condition. Based on the cultivation of this character, children are more confident and then children can also communicate well with their peers and friends in other classes. Implementation for further research is a study of the effectiveness of audio and audiovisual based stories in early childhood to instill strategic good values ​​to be developed.